Identification and expression of key genes related to 1-deoxynojirimycin biosynthesis in Streptomyces lavendulae - Xiangdong Xin; Xueping Jiang; Baoxin Niu; Minqi Zhang; Xueming Xu; Ran Zhang; Hao Li; Zhongzheng Gui (Electronic Journal of Biotechnology, 2023)
Background: Streptomyces lavendulae is a bacterium that produces 1-deoxynojirimycin (DNJ), an alkaloid with various beneficial pharmacological properties. While a putative DNJ biosynthesis metabolite pathway has been proposed for this bacterium, the related key genes have not yet been identified. Results: In this study, DNJ production during S. lavendulae fermentation was induced by mulberry seed extracts and the key genes related to DNJ biosynthesis under those experimental conditions were identified using transcriptome sequencing. Gene expression was then analyzed using real-time qPCR, and related to metabolite levels in the DNJ pathway. The mulberry seed polysaccharide extract (MSP) induced DNJ yield in S. lavendulae broth more effectively than the mulberry seed alkaloid and flavonoid extracts. Supplementation with 3.00 mg/mL MSP resulted in 27.19 μg/mL DNJ, which was 8.55 times than that in the control group (3.18 μg/mL). Transcriptome sequencing revealed 2328 differentially expressed genes (DEGs) in MSP vs. unsupplemented-control comparisons, of which 1151 DEGs were up-regulated and 1177 DEGs were down-regulated in MSP. Functional enrichment analysis revealed four pathways of DNJ biosynthesis. Six key genes related to DNJ biosynthesis were then validated using real-time qPCR and the analysis of intermediate metabolites. These were, aspC, encoding a putative transaminase that produces 2-amino-2-deoxy-d-mannitol-6-phosphate; MJ0374-1 and MJ0374-2, encoding a phosphatase that produces 2-amino-2-deoxy-d-mannitol; and frmA-1, frmA-2, and adhD, which encode a Zn-dependent dehydrogenase that produces mannojirimycin. Conclusions: This is the first study to identify the genes relevant for DNJ biosynthesis in S. lavendulae, and it paves the way for engineering the bacterium to achieve for industrial-scale DNJ production. How to cite: Xin X, Jiang X, Niu B, et al. Identification and expression of key genes related to 1-deoxynojirimycin biosynthesis in Streptomyces lavendulae. Electron J Biotechnol 2023; 64. https://doi.org/10.1016/j.ejbt.2023.03.003.